Proteomic Screening and Verification of Biomarkers in Different Stages of Mycosis Fungoides: A pilot Study - Gan, Lu; Shi, Haoze; Zhang, Ying; Sun, Jianfang; Chen, Hao (Frontiers in Cell and Developmental Biology, 2021)
Mycosis fungoides (MF) is the most common cutaneous T-cell lymphoma; in advanced stages, it can involve multiple organs and has a poor prognosis. Early detection of the disease is still urgent, but there is no optimal therapy for advanced MF. In the present study, quantitative proteomic analyses (label-free quantitation, LFQ) were applied to tissue samples of different stages of MF and tissue samples from controls (eczema patients and healthy donors) to conduct preliminary molecular analysis to clarify the pathogenesis of the disease. Differential protein expression analysis demonstrated that 113 and 305 proteins were associated with the early and advanced stages of MF, respectively. Gene ontology (GO) enrichment analysis was conducted to determine the potential functions of the proteins, which could be classified into three categories: biological process, cellular component, and molecular function. The results revealed that a series of biological processes, including ‘initiation of DNA replication’ and ‘nucleosome assembly’, were involved in the disease. Moreover, cellular components, including the ‘desmosome’ and ‘integrin complex’, may affect the invasion and metastasis of MF via molecular functions, including ‘integrin binding’ and ‘cadherin binding’ . Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis demonstrated that ‘focal adhesion DNA replication’, ‘Toll-like receptor signalling pathway’ and other pathways were also involved. A parallel reaction monitoring (PRM) assay was applied to validate the identified differentially expressed proteins . In conclusion, the above proteomic findings may have great diagnostic and prognostic value in diverse malignancies, especially MF. Nevertheless, further studies are still needed to explore the precise mechanisms of MF.